Structural Behavior of Composite Castellated Steel Concrete Beams Subjected to Impact Load (Journal of University of Babylon for Engineering Sciences, 2018)
The structural behavior of composite castellated steel concrete beams subjected to impact load presented in this study. In which fabrication of composite castellated steel self-compacting concrete beams which connected to self-compacting concrete by means of stud shear connectors. Four composite castellated beams were performed with different degrees of castellation, they were 0%, 25%, 33.8% and 50%. These specimens were subjected to an impact load produced from free falling of steel ball. The experiments required fabrication of special rig which connected with different sensors and programmed by Lab VIEW 2016 program. Different parameters were recorded and discussed which involved force-time history and displacement history for the tested beams. It is founded that the increase of the degrees of castellation for the adopted specimens will increase the maximum impact load by about 16.13%, compared with non-castellated composite specimen. The amplitudes of vibration represented by displacement have decreased with the increasing of degrees of castellation by about 3.51%, 14.04% and 20.18% for the degrees of castellation 25%, 33.8%, and 50% respectively.